Association between joint exposure to ambient air pollutants and carotid plaque: The mediating role of cardiometabolic risk factors - Yunfei Li; Ze Han; Xiaoyu Zhao; Yueruijing Liu; Zhiyuan Wu; Jinqi Wang; Xia Li; Xiuhua Guo; Lixin Tao (Ecotoxicology and Environmental Safety)
Background: Research has shown that exposure to joint air pollution is related to atherosclerosis, but little evidence has been found for carotid plaques. Our objective is to assess the association between exposure to joint air pollutants and carotid plaque and explore the mediating role of cardiometabolic factors in this relationship. Methods: The Beijing Health Management Cohort (BMHC) study followed participants recruited from 2013 to 2014 until December 31, 2020. All participants underwent carotid ultrasound and were free of carotid plaque at baseline. A satellite-based land-use regression (LUR) model was applied to estimate air pollution exposure. The joint exposure to air pollutants was assessed by incorporating a weighted air pollution score. A modified Poisson regression model was conducted to investigate the relationship between exposure to air pollution and carotid plaque occurrence. Mediation analysis explored how cardiometabolic factors mediate the relationships between exposure to joint air pollution and carotid plaque risk. Results: During an average follow-up period 4 years, 1240 cases of carotid plaque were identified among 7358 participants. Each interquartile range (IQR) increase in air pollutants was associated with the following relative risk (RR) and 95 % confidence intervals (95 % CIs) for carotid plaque: 2.5-micrometer particulate matter (PM2.5), 1,04 (1.01, 1.07), 10-micrometer particulate matter (PM10), 1.10 (1.01, 1.20), sulfur dioxide (SO2), 1.28 (1.15, 1.42), ozone (O3), 1.18 (1.01, 1.37), and carbon monoxide (CO), 1.32 (1.15, 1.50). Joint exposure to air pollution was positively and linearly associated with the occurrence of carotid plaque, with low-density cholesterol (LDL-C) and mean arterial pressure (MAP) mediating 2.24 % and 4.28 % of the association, respectively. Conclusions: Long-term joint exposure to ambient air pollutants elevates the risk of developing carotid plaque. LDL-C and MAP suggest partial mediating effects of joint air pollution on carotid plaques. Our results emphasize the need to thoroughly evaluate various air pollutants concerning carotid plaque.